Psychological Readiness of Intrinsic Motivation for the Second Language Leaners - Win Listyaningrum Arifin (IJIP : Indonesian Journal of Islamic Psychology, 2023)
This paper aims at answering on how intrinsic motivation has affected the second language learners and on why this intrinsic motivation has influenced the acquisition and the competence toward the language mastery. By applying a descriptive qualitative approach taken from 10 interviews to the third semester students of English Department of Islamic State University Salatiga, this paper also uses library research from papers to be analyzed and organized to set the conclusion. From the result, it is concluded that intrinsic motivation is the most dominant factor for the students to study foreign language, here English. Therefore, this motivation seems complicated when both the lecturer and the supporting environment were absence. Later, this motivation contributes to the competence owned by the students which is supported by the awareness to be more engaged and active in the language learning and acquisition process.